Performance of High TSS Onion Varieties in Telangana - Goud, R. Preetham; Kumari, D. Anitha; Suresh, Veera; Nikhil, B. S. K.; Mamatha, A. (International Journal of Bio-resource and Stress Management, 2024)
Field experiments were conducted at Vegetable Research Station, Hyderabad, India during rabi seasons (October–March) of 2019–20, 2020–21 and 2021–22 to study the performance of high TSS varieties of onion in initial evaluation trial, advanced varietal trial-I and advanced varietal trial-II as part of All India Network Research Project on Onion and Garlic. The entries tested were DOGR-HT-1, DOGR-HT-2, DOGR-HT-3, DOGR-HT-4, Agrifound White, PKV White and Bhima Shweta. The predominant colour of all the entries was white and the predominant shape of the bulbs was oval. High amount of uniformity in bulb size was reported by Bhima Shweta and PKV white, while the rest of the entries DOGR-HT-1, 2, 3, 4 and Agrifound White reported average uniformity in bulb size. Among the seven entries tested DOGR-HT-2 reported the highest TSS value (17.77 °Brix) followed by DOGR-HT-3 (15.30 °Brix) and the least TSS value was reported by DOGR-HT-1. Maximum mean bulb weight (100.73 g), marketable yield (49.03 tha-1) and total yield (50.48 t ha-1) was reported by Bhima Shweta and it was followed by PKV White (100.26 g, 48.99 t ha-1 and 50.28 t ha-1). The least average bulb yield (84.31 g), marketable yield (41.09 t ha-1) and total yield (42.34 t ha-1) was reported by DOGR-HT-2 but was at par with DOGR-HT-3 and DOGR-HT-4. Minimum incidence of thrips and purple blotch were noticed in DOGR-HT-4.